2021
DOI: 10.1038/s41598-021-82053-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid indices as simple and clinically useful surrogate markers for insulin resistance in the U.S. population

Abstract: This study aimed to compare the accuracy of novel lipid indices, including the visceral adiposity index (VAI), lipid accumulation product (LAP), triglycerides and glucose (TyG) index, TyG-body mass index (TyG-BMI), and TyG-waist circumference (TyG-WC), in identifying insulin resistance and establish valid cutoff values. This cross-sectional study used the data of 11,378 adults, derived from the United States National Health and Nutrition Examination Survey (1999–2016). Insulin resistance was defined as a homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…Lipid indices, which can be easily calculated with routine laboratory tests, may be useful markers for insulin resistance risk assessments in clinical settings, according to Lee et al. 33 . The triglyceride to HDL ratio allow identification of the insulin-resistant metabolic state, and a high TG:HDL-C ratio at baseline may be a useful surrogate indicator of future Type 2 Diabetes, as reported by Lim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid indices, which can be easily calculated with routine laboratory tests, may be useful markers for insulin resistance risk assessments in clinical settings, according to Lee et al. 33 . The triglyceride to HDL ratio allow identification of the insulin-resistant metabolic state, and a high TG:HDL-C ratio at baseline may be a useful surrogate indicator of future Type 2 Diabetes, as reported by Lim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the gold standard HIEG clamp and other surrogate markers of IR, which are complicated, time- and cost-consuming, and glucose and insulin dependent, VAI exhibited the superiority of simplicity, accessibility, inexpensiveness, and glucose and insulin independent. Studies have confirmed the significant correlation between VAI and HIEG clamp and the HOMA-IR ( 9 , 10 ), suggesting the great potential of VAI as a useful indicator to accurately reflect the level of IR.…”
Section: Discussionmentioning
confidence: 87%
“…Former studies have shown that IR is usually characterized as glycometabolic abnormality, lipometabolic disturbance, and visceral obesity ( 8 ). Given these characteristics, a calculated surrogate parameter called visceral adiposity index (VAI), which is determined by waist circumference (WC), body mass index (BMI), fasting triglyceride (TG), and high-density lipoprotein cholesterol (HDL-C), was proposed and shown to be highly related to the hyperinsulinemic-euglycemic (HIEG) clamp and the homeostasis model assessment of IR (HOMA-IR), the gold standard and frequently used methods for assessing IR ( 9 , 10 ). Previous studies have demonstrated that there is a positive association between the level of VAI and the risk of atherosclerosis ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kumpatla et al confirmed that 2.3 is the cut-off value of VAI, with 62.1% sensitivity and 59.7% specificity for detecting glucose intolerance 40 . Juncheol et al that reported the cut-off values were as follows: VAI: men 1.65, women 1.65 41 . As a lipid combined anthropometric indices, VAI can be obtained in the routine medical examination center.…”
Section: Discussionmentioning
confidence: 99%